Residential and socio-economic difference in protein intake of children aged 6-35 months in Indonesia: The national individual food consumption survey 2014 - Mauludyani Anna V. R.; Suparmi Suparmi; Wibowo Yulianti (BIO Web of Conferences)
Consumption of protein by young children is known to support children’s growth and weight gain and thus may help prevent stunting. This study aimed to investigate variation in protein consumption between age groups, socioeconomic status (SES), and residential type among children aged 6-35 months in Indonesia. We analyzed data from the National Individual Food Consumption Survey (SKMI) 2014, which included 3,449 children. Our findings revealed that protein intake increased with children’s age in both urban and rural, ranging from 14.9 to 42.5 g/d in urban areas and 12.6 to 40.3 g/d in rural areas. In both urban and rural settings, protein intake increases significantly with better SES, from 33.4 to 37.8 g/d and 31.6 to 39.5 g/d, respectively. More younger children (6-11 months) had protein inadequacy than older age (73.9 vs 17.6% in urban and 82.8 vs 24.4% in rural areas). Conversely, older children from all SES had mean protein intake higher than the RDA. The primary protein sources were cereals (i.e. rice, plant protein), followed by offal, fish, and meat. This suggests that nutrition education along with improving protein consumption by younger children is crucial for growth and development as well as preventing stunting.